Thirsty seafarers at Temple B of Kommos : commercial districts and the role of Crete in Phoenician trading networks in the Aegean - Sogas, Judith Muñoz, (Archaeopress Archaeology, 2022)
The island of Crete was an important place for cultural and economic exchanges between Greeks and Near Easterners in the Aegean during the 1st millennium BC. This book aims to understand the Phoenician presence and trade in Aegean temples, as well as how Crete shaped its role within the context of Mediterranean trade routes from East to West.